Analisis Rantai Pasok Kopi Arabika di UPH Pusparahayu Kecamatan Cigalontang Kabupaten Tasikmalaya - Sumiati, Tita; Nuraini, Candra; Noormansyah, Zulfikar; Apriyani, Dwi (Universitas Galuh, 2024)
This research aims to know the general description of the supply chain and the performance of the Arabica coffee supply chain at UPH Pusparahayu, Cigalontang District—, using descriptive qualitative and quantitative methods. The location for the research was determined purposively, namely at UPH Pusparahyu, because it acts as the most significant coffee processing unit in the area and accommodates supplies from many farmers. The method of data analysis to find out the general description of the supply chain uses the concept of Food Supply Chain Networks (FSCN). Supply chain performance measurement was analyzed using the Supply-Chain Operations Reference (SCOR) method, which has five assessment attributes: reliability, responsiveness, flexibility, assets, and cost. The results of the study show an overview of the Arabica coffee supply chain in Cigalontang District, among others targeting the domestic market; the market structure consists of farmers, UPH Pusparahayu, and coffee shops; business process refers to a push or pull view with a variety of modern resources at the UPH level; and have supply chain management that is still conventional in terms of contracts and partner selection. Supply chain performance at the farm level for reliability, responsiveness, flexibility, and assets has reached a superior position, but the cost attribute is in a place of parity. In contrast, the results of performance measurements at the UPH level show an excellent post on reliability, responsiveness, and flexibility. Meanwhile, the asset and cost attributes have not reached the best position.